Capybara responses to varying levels of predation risk. (August 2022) - Avila, Ana Belen; Corriale, María Jose; Donadio, Emiliano; Di Bitetti, Mario S.; Ponzio, Marina F.; Cantarelli, Veronica; De Angelo, Carlos
Abstract : Predators can generate physiological and behavioural responses in prey individuals. Thus, carnivore reintroductions might cause profound changes in communities and ecosystems by modifying antipredator responses. Combining observational and experimental approaches, we compared the short- and long-term antipredator responses of capybaras, Hydrochoerus hydrochaeris, between a landscape with a high density of predators (Pantanal, Brazil) and a landscape where predators became extinct in the mid-20th century but where a jaguar reintroduction project was in progress (Iberá, Argentina). Generalized linear models were used to test whether the presence of natural predators affects capybara behavioural budgets, gregarious behaviour and the associated physiological stress responses and to test whether, in the short term, capybaras increase their vigilance levels after detecting the proximity of a simulated predator (a playback of jaguar, Panthera onca, calls). Capybaras in the Pantanal did not show higher levels of vigilance but they spent a greater proportion of time foraging than did capybaras in Iberá. Pantanal groups were smaller and foraged closer to water. The baseline levels of stress hormones tended to be higher in Iberá. In response to simulated stimuli, both populations responded to predator sound cues by increasing vigilance, but Iberá groups also increased vigilance in response to a control sound, suggesting that they did not recognize the predator stimulus as a greater risk than another stimulus. In areas with predators, capybaras may reduce predation risk by choosing safer areas, where they can spend more time foraging when predators are not nearby. Vigilance may be only a reactive response to cues of the predator's proximity. Understanding the capybara's antipredator responses may help predict the potential effects and the success of jaguar reintroduction in a region where the jaguar has been absent for over 80 years. Highlights: Capybaras facing regular jaguar predation spent more time foraging in safe zones. Capybaras living without predators did not recognize predator sound stimuli. Vigilance may be only a reactive response to cues of the predator's proximity. Prey released from predation for generations may lose some antipredator behaviours. Naïvety and high density of capybaras could predict successful jaguar reintroduction.